Improving Reading Literacy Using Foreign Methods in Primary Education - Raximqulova Maxbuba Baxronovna; Xudaykulov Jamshid Nishanovich (Zien Journals, 2023)
The Standard Of Competence And Skills Required In Each Class In Terms Of The Four Main Types Of Speech Activities Acquired By Teaching The Language To The Student: Listening Comprehension, Speaking, Reading And Writing
Keywords: Language; Speaking; Reading And Writing